A linear actuator for precision positioning of dual objects. (13th November 2015) - Peng, Yuxin; Cao, Jie; Guo, Zhao; Yu, Haoyong
Abstract: In this paper, a linear actuator for precision positioning of dual objects is proposed based on a double friction drive principle using a single piezoelectric element (PZT). The linear actuator consists of an electromagnet and a permanent magnet, which are connected by the PZT. The electromagnet serves as an object 1, and another object (object 2) is attached on the permanent magnet by the magnetic force. For positioning the dual objects independently, two different friction drive modes can be alternated by an on–off control of the electromagnet. When the electromagnet releases from the guide way, it can be driven by impact friction force generated by the PZT. Otherwise, when the electromagnet clamps on the guide way and remains stationary, the object 2 can be driven based on the principle of smooth impact friction drive. A prototype was designed and constructed and experiments were carried out to test the basic performance of the actuator. It has been verified that with a compact size of 31 mm ( L ) × 12 mm ( W ) × 8 mm ( H ), the two objects can achieve long strokes on the order of several millimeters and high resolutions of several tens of nanometers. Since the proposed actuator allows independent movement of two objects by a single PZT, the actuator has the potential to be constructed compactly.